Level of satisfaction of external users hospitalized in a national police hospital - Zárate-López, María M. (2018)
Objective: To identify the level of satisfaction of the external users hospitalized in the general surgery and internal medicine services of a National Police Hospital. Methods: Observational, descriptive, comparative cross-sectional study. Independent variables: dimensions of quality, dependent variable: level of satisfaction and intervening variables: sex, age, level of education, hospitalization services (internal medicine and general surgery). Out of 377 hospitalized patients, 363 met the selection criteria, the modified SERVQUAL survey was applied. Inferential statistics and measures of descriptive frequency were used. Results: The external users that predominated were: adults and older adults, with educational level between secondary and higher; a minimum percentage were illiterate and young adults. The female sex predominated in the internal medicine service and the male sex in the general surgery service. The perception of satisfaction was higher in female patients, older adults and higher university level of education. The dimensions with greater satisfaction in both services were reliability, responsiveness, security and empathy. The level of satisfaction of external users was greater than 70% in the general surgery service and greater than 90% in the internal medicine service. Conclusion: The external users of both hospitalization services were satisfied, covering their needs and demands, exceeding their expectations. Key words: Quality; Satisfaction; External user; Hospitalization. (source: MeSH NLM)   DOI: 10.25176/RFMH.v18.n2.1285